2020
DOI: 10.3390/ma13102348
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Study of a Mg–Zn–Zr Alloy Hot Compressed at a High Strain Rate

Abstract: Understanding the correlation of plasticity with deformation and dynamic recrystallization (DRX) behaviors, in magnesium (Mg) alloys deformed under high-strain-rate conditions, is increasingly important for wrought Mg processing. In the present study, a ZK30 (Mg-2.61%Zn-0.66%Zr by weight percent (wt.%)) alloy in the as-forged state was hot compressed to various strain levels at a temperature of 350 °C and a strain rate of 10 s−1. Heterogeneous deformation and dynamic recrystallization (DRX) behaviors of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The homogenized material was characteristic of coarse grains with grain size of 400 µm, and few twins were detected (Figure 1). X-ray diffraction results show that the homogenized material has a nearly random texture (Figure 2), the relative intensities of the ( 0002 successfully carried out on Mg-Al-Zn [4,5], Mg-Zn-Zr [6,7], Mg-RE [8,9] alloys and pure magnesium [10]. These research studies reported that high strain rate facilitates high density twinning which subsequently induces dynamic recrystallization (DRX); the twinning and DRX can release stress and consume strain energy induced by plastic deformation, and consequently results in remarkable improvement in the formability of the alloys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The homogenized material was characteristic of coarse grains with grain size of 400 µm, and few twins were detected (Figure 1). X-ray diffraction results show that the homogenized material has a nearly random texture (Figure 2), the relative intensities of the ( 0002 successfully carried out on Mg-Al-Zn [4,5], Mg-Zn-Zr [6,7], Mg-RE [8,9] alloys and pure magnesium [10]. These research studies reported that high strain rate facilitates high density twinning which subsequently induces dynamic recrystallization (DRX); the twinning and DRX can release stress and consume strain energy induced by plastic deformation, and consequently results in remarkable improvement in the formability of the alloys.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, low strain rate is adopted for magnesium alloys during the deformation, and as a result, it is costly and inefficient to produce magnesium alloy applications with traditional deformation processes [3]. In recent research, high strain rate deformation was successfully carried out on Mg-Al-Zn [4,5], Mg-Zn-Zr [6,7], Mg-RE [8,9] alloys and pure magnesium [10]. These research studies reported that high strain rate facilitates high density twinning which subsequently induces dynamic recrystallization (DRX); the twinning and DRX can release stress and consume strain energy induced by plastic deformation, and consequently results in remarkable improvement in the Materials 2020, 13, 3050 2 of 12 formability of the alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The advantageous properties could be attained only if the reinforcements are distributed homogeneously and not clustered in the matrix. According to the literature available [ 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ], limited research has been performed on CNT-reinforced MMCs due to difficulties in fabricating and dispersion of CNTs in the matrix. Most studies investigated the fabrication methods such as the casting process and powder metallurgy for developing Mg-based alloy [ 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 ,…”
Section: Summary and Future Road Mapsmentioning
confidence: 99%
“…The aforementioned merits made RS Mg-6Zn-5Ca-3Ce alloy a potential Mg alloy. However, the subsequent processing capability of RS Mg-Zn-Ca-Ce alloy is still limited due to inadequate slip systems at ambient temperature [9][10][11] and plentiful hardbrittle phases [4] . Fortunately, as the temperature increases, the workability of Mg alloys will be improved greatly owing to the activation of non-basal slip [12] and grain boundary slip [13].…”
Section: Introductionmentioning
confidence: 99%